Gas phase hydrogenation of furfural to obtain valuable products using commercial Cr-free catalysts as an environmentally sustainable alternative to copper chromite - Jiménez-Gómez, Carmen Pilar; Cecilia-Buenestado, Juan Antonio; García-Sancho, Cristina; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (Elsevier, 2021)
Traditionally, copper chromite has been used in furfural hydrogenation to obtain valuable products, like furfuryl alcohol. However, the presence of Cr poses serious environmental issues, in such a way that different Cr-free catalysts have been proposed as alternative. In this work, two commercial Cu-based catalysts without Cr, currently used in alcohol reforming (R120) and water-gas shift (W220), have been successfully evaluated in FUR hydrogenation to produce selectively furfuryl alcohol. Both R120 and W220 catalysts were characterized, with special emphasis on the elucidation of metallic properties, dispersion and oxidation states of Cu species, and compared to copper chromite. The R120 catalyst attained the best catalytic performance and stability over time, reaching a turnover frequency (TOF) of 0.31 s−1 at 190 °C, after 1 h of reaction. The catalytic results demostrated that these Cr-free commercial catalysts have high potential to replace copper chromite as shown the stability test for 24 h.
https://openpolicyfinder.jisc.ac.uk/id/publication/29690?from=single_hit
Keywords: Hidrogenación; Aldehídos; Furfural; Hydrogenation; Cu/ZnO/Al2O3; Furfuryl Alcohol; 2-methylfuran